Patterns of scheduled follow-up appointments following hospitalization for heart failure: insights from an urban medical center in the United States - Goyal P (Dove Medical Press, 2016)
Parag Goyal,1 Madeline R Sterling,2 Ashley N Beecy,2 John T Ruffino,2 Sonal S Mehta,3 Erica C Jones,1 Mark S Lachs,3 Evelyn M Horn1 1Division of Cardiology, Department of Medicine, 2Department of Medicine, 3Division of Geriatrics, Department of Medicine, Weill Cornell Medicine, New York, NY, USA Objectives: Although postdischarge outpatient follow-up appointments after a hospitalization for heart failure represent a potentially effective strategy to prevent heart failure readmissions, patterns of scheduled follow-up appointments upon discharge are poorly described. We aimed to characterize real-world patterns of scheduled follow-up appointments among adult patients with heart failure upon hospital discharge.Patients and methods: This was a retrospective cohort study performed at a large urban academic center in the United States among adults hospitalized with a principal diagnosis of congestive heart failure between January 1, 2013, and December 31, 2014. Patient demographics, administrative data, clinical parameters, echocardiographic indices, and scheduled postdischarge outpatient follow-up appointments were collected.Results: Of the 796 patients hospitalized for heart failure, just over half of the cohort had a scheduled follow-up appointment upon discharge. Follow-up appointments were less likely among patients who were white and had heart failure with preserved ejection fraction and more likely among patients with Medicaid and chronic obstructive pulmonary disease. In an adjusted multivariable regression model, age ≥65 years was inversely associated with a scheduled follow-up appointment upon hospital discharge, despite higher rates of several cardiovascular and noncardiovascular comorbidities.Conclusion: Just half of the patients discharged home following a hospitalization for heart failure had a follow-up appointment scheduled, representing a missed opportunity to provide a recommended care transition intervention. Despite a greater burden of both cardiovascular and noncardiovascular comorbidities, older adults (age ≥65 years) were less likely to have a follow-up appointment scheduled upon discharge compared with younger adults, revealing a disparity that warrants further investigation. Keywords: appointments, patient readmission, ageism, heart failure